Designation of Pseudobiotus kathmanae Nelson, Marley & Bertolani, 1999 as the type species for the genus Pseudobiotus Nelson, 1980 (Tardigrada) - Marley, Nigel J.; Bertolani, Roberto; Nelson, Diane R. (Zootaxa, 2008)
The contents of the application to the International Commission of Zoological Nomenclature, case 3017, are presented with an explanation of how its publication fell between the third and fourth editions of the Code. In so doing, the genus Pseudobiotus Nelson, 1980 (In: Schuster, Nelson, Grigarick & Christenberry, 1980) was left without a type species, which is hereby designated under article 70 of the fourth edition of the code.